Myths of Oceania - Dalal, Anita (Austin, TX Brown Partworks Limited, 2002)
Presents some of the mythology of Oceania, particularly Polynesia and Australia, and gives some background information on the peoples there.
Includes bibliographical referenes and index.
9 - 12 years
82070
Keywords: Mythology -- Polynesian -- Juvenile literature; Mythology -- Australian aboriginal -- Juvenile literature; Oceania -- Juvenile literature